2012
DOI: 10.1063/1.4751862
|View full text |Cite
|
Sign up to set email alerts
|

Single-mode lasing of GaN nanowire-pairs

Abstract: Stable single-mode lasing operation from a pair of coupled GaN nanowires is demonstrated through optical pumping. GaN nanowires with different lengths were placed side-by-side in contact to form a coupled cavity through nanoprobe manipulation. Unlike individual nanowire lasers, which operate in a combined multiple transverse and multiple longitude mode oscillation, a coupled nanowire-pair provides a mode selection mechanism through the Vernier effect, which can strongly enhance the free spectrum range between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 21 publications
0
54
1
Order By: Relevance
“…A minimum spacing of $0.58 nm is observed, much smaller than the calculated longitudinal mode spacing of $2.1 nm for single transverse-mode operation. 9 Taken together, these spectral features are indicative of multiple transverse-mode operation of the GaN nanowire laser. 9 Fig.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…A minimum spacing of $0.58 nm is observed, much smaller than the calculated longitudinal mode spacing of $2.1 nm for single transverse-mode operation. 9 Taken together, these spectral features are indicative of multiple transverse-mode operation of the GaN nanowire laser. 9 Fig.…”
mentioning
confidence: 91%
“…9 In order to obtain single-mode operation, it is necessary to introduce a multimode suppression technique to the nanowire cavity. Previously, we have demonstrated that multiple longitudinal-mode oscillation in GaN nanowires can be suppressed by reducing the nanowire length to $5 lm, at which point the mode competition is strongly enhanced in the cavity.…”
mentioning
confidence: 99%
“…Mode selection was performed and only one mode was stimulated at the end using two GaN nanowires coupled side by side [110]. Yang et al from Berkeley University followed the same principles, except for performing the coupling axially rather than radially [29].…”
Section: (C) Single-mode Selectionmentioning
confidence: 99%
“…In order to maximize the potential of nanowire lasers, a greater understanding and control over their properties, including mode control, polarization control, wavelength tuning, and beam shaping, is necessary. Recently, single mode emission from GaN nanowire lasers was demonstrated via several routes, including size (diameter and length) control 6 , coupled nanowires [7][8][9] , distributed feedback 10 , and placement onto a metal substrate, which induces a mode-selective loss 11 . Wavelength tuning of GaN nanowire lasers was demonstrated using GaN/InGaN nanowire photonic crystal arrays 12,13 , hydrostatic pressure 14 , and bandgap graded nanowires 15,16 .…”
Section: Table Of Contents Figurementioning
confidence: 99%